Comparison of prey availability for Setophaga petechia gundlachi(Aves: Parulidae) between two mangroves with different vegetation structure - Alejandro Rodríguez-Ochoa; Martín Acosta Cruz (Caldasia)
The subspecies Setophaga petechia gundlachi is characterized by its specificity to mangrove habitat during the breeding season. The objective of this work was to compare the prey availability for S. petechia gundlachi during the breeding season in two mangrove sites with different vegetation struc-ture in Havana, Cuba. To describe different levels of vegetation structure between both mangrove sites, we took several variables at 50 plots. Besides, we recorded the foraging behavior of S. petechia gundlachito establish the design of prey availability sampling. We measured prey availability by using the branch clipping method, about 90 samples were collected at each mangrove site. Bajo de Santa Ana mangrove, with a lower height and diameter at breast height, showed evidence of deforestation. Laguncularia racemosa was the most used mangrove species for foraging and offered the highest biomass of available prey in the Laguna de Cobre-Itabo mangrove site. The greatest biomass of available prey was found at the Laguna de Cobre-Itabo, with a value of 5.1 (CI: 4.0 - 6.2) mg / 100 g of branch clipping. The Bajo de Santa Ana site had a lower value than expected 1.6 (CI: 0.8 - 1.7) mg / 100 g of branch clipping. The results provide evidence of the possible influence of mangrove vegetation structure changes on food availability for S. petechia gundlachi in this urban landscape.